New reconstruction of annual integral solar proton fluences between 1984--2019 - Usoskin, Ilya; Raukunen, Osku; Koldobskiy, Sergey; Kovaltsov, Gennady; Vainio, Rami (Italy, 2025)
Accurately determining the long-term fluxes and variability of solar energetic particles (SEPs) is crucial for understanding space physics. However, there are significant uncertainties in assessing average SEP fluxes over the past decades using different methods and datasets. In this study, we aim to re-evaluate annual integral SEP fluences using in-situ measurements from 1984 to 2019, covering three solar cycles 22 – 24. We reconstructed a comprehensive time series of integral SEP fluxes above various energy thresholds (10, 30, 60, 100, and 200 MeV) based on observations from the GOES satellites. To ensure a consistent dataset, we performed intercalibration of the fluxes by establishing linear relations between overlapping observations. Precise calculations of annual SEP fluences were obtained through careful subtraction of galactic cosmic ray (GCR) background and identification of SEP event periods. We calculated annual integral fluences of SEPs for the period spanning 1984 to 2019 at different energy thresholds. Our analysis revealed that solar cycle 24 exhibited a significantly weaker SEP fluence (5 to 8 times lower) compared to cycles 22 and 23.